Entering PIN codes by smooth pursuit eye movements (Journal of Eye Movement Research, 2014)
Despite its potential gaze interaction is still not a widely-used interaction concept. Major drawbacks as the calibration, strain of the eyes and the high number of false alarms are associated with gaze based interaction and limit its practicability for every-day human computer interaction. In this paper two experiments are described which use smooth pursuit eye movements on moving display buttons. The first experiment was conducted to extract an easy and fast interaction concept and at the same time to collect data to develop a specific but robust algorithm. In a follow-up experiment, twelve conventionally calibrated participants interacted successfully with the system. For another group of twelve people the eye tracker was not calibrated individually, but on a third person. Results show that for both groups interaction was possible without false alarms. Both groups rated the user experience of the system as positive.